Five years of regional risk pooling: An updated cost-benefit analysis of the African risk capacity - Kramer, Berber; Rusconi, Rob; Glauber, Joseph W. (International Food Policy Research Institute, 2020)
An initial cost-benefit analysis (CBA) of the African Risk Capacity (ARC), published in 2013, showed that regional risk pooling for severe droughts could increase benefits to poor households by as much as US$ 1.90 per dollar invested, due to the speed, cost and targeting gains from improved risk financing and contingency planning of a humanitarian response. We revisit the assumptions underpinning this initial CBA to reflect current ARC operations, and we update the CBA using new methods for evaluating the costs and benefits of regional risk pooling to finance disaster risk management. Under the revised methods and assumptions, the increase in benefits to the poor will have exceeded the costs of regional risk pooling, but not by as much as US$ 1.90 per dollar invested. This is because ARC premiums have been higher than assumed in the initial CBA, and insured countries have used ARC payouts mainly to distribute food aid, instead of leveraging state-contingent welfare schemes with potentially larger speed, cost and targeting gains. We discuss potential ways to lower premiums and strengthen the benefits to poor households, highlighting also the potential to realize welfare gains from improved risk management and investments ex ante, even during years without insurance payout.